2018
DOI: 10.3390/ijerph15112493
|View full text |Cite
|
Sign up to set email alerts
|

Customer Purchase Intentions and Choice in Food Retail Environments: A Scoping Review

Abstract: Food purchasing and consumption behaviors have implications for nutrition and obesity. Food retail environments, in particular, shape customer food choices and energy intake. The marketing literature offers insights about how public health practitioners can work within food retail environments to encourage healthy food choices. We reviewed experimental studies in the marketing literature to examine factors influencing customer purchase intentions and choice for food products in retail stores. Database searches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 60 publications
1
56
0
3
Order By: Relevance
“…The choice of food products and purchase decisions are influenced by a number of factors, including those related to health [47], nutritional knowledge [48], and the place where the product is purchased [49], but convenience and preferences may be the crucial ones [50]. This was confirmed by the results of a study by Horning et al [51], where it was observed that the common reasons for choosing pre-packed processed meals instead of non-processed ones are preferences and time.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of food products and purchase decisions are influenced by a number of factors, including those related to health [47], nutritional knowledge [48], and the place where the product is purchased [49], but convenience and preferences may be the crucial ones [50]. This was confirmed by the results of a study by Horning et al [51], where it was observed that the common reasons for choosing pre-packed processed meals instead of non-processed ones are preferences and time.…”
Section: Discussionmentioning
confidence: 99%
“…The products of the food and wine supply chain are considered elements that are capable of offering the tourist a direct expression of a culture, and can be capable of generating tourist flow. From a marketing point of view, the product can be promoted and used as a means of tourist and gastronomic attraction [88][89][90].…”
Section: Resultsmentioning
confidence: 99%
“…However, an alternative for future researchers interested in supermarkets food environment research is the use of simulated, or virtual, stores to test intervention strategies for eventual buy-in from supermarkets [10]. Additionally, formative research and/or adaptive intervention approaches should be conducted to understand how to influence product availability and placement within stores given previous evidence demonstrating the relationship between these dimensions and dietary behaviors [11,12,37,67]. One potential way to effectively manipulate multiple aspects of the in-store environment is by involving multiple partners [58,68].…”
Section: Resultsmentioning
confidence: 99%